Analysis of Needs for Development of Android-Based Socioscientific Issues Teaching Materials on the Topic of Climate Change to Improve Students' Decision-Making Ability - Suci Indah Putri; Ida Hamidah; Winny Liliawati (Postgraduate, University of Mataram, 2023)
Teaching materials are vital recources for students in their learning process. Decision-making skills are one of the essential competencies that students have to possess in the 21st century. The global dilemmas being faced today and will get worse is climate change. The challenges caused by climate change that is occurring need to involve students looking for the best decisions as well as through these problems students will be able to train their decision-making abilities. This study aimed to analyze the importance of developing socio-scientific issues teaching materials to train decision-making skills so that later it will be improved. Data were collected through questionnaires filled out by 30 students to gauge their current decision-making abilities, revealing a tendency to rely on personal feelings. Additionally, 10 teachers were surveyed about their methods for enhancing students’ decision-making skills. This data was analyzed using descriptive analysis. The results of the study found that the level of students' ability to make decisions is still low and based on their personal feelings. Also, there were no teaching materials containing socioscientific-issues to train students' decision-making skill. Thus, it is important to develop android-based socioscientific-issues teaching materials on the topic of climate change to improve students' decision-making skills.